The effects of self-controlled and instructor-controlled feedback on motor learning and intrinsic motivation among novice adolescent taekwondo players - Reza Goudini; Saeed Ashrafpoornavaee; Alireza Farsi (Palacký University Olomouc, 2019)
Background: Although the useful effects of self-controlled feedback on motor skills learning have been proven, a study dealing with the effects of self-controlled and instructor-controlled feedback on learning and intrinsic motivation among novice taekwondo players has so far not been conducted. Objective: The purpose of the present study was to examine the effects of self-controlled and instructor-controlled feedback on learning the ap chagi technique and intrinsic motivation among novice adolescent taekwondo players. Methods: Thirty participants (12.43 ± 2.08 years) were selected purposefully and homogeneously based on pre-test scores. They were categorized in the three groups, namely self-control, yoked, and instructor-control. The acquisition phase consisted of 100 ap chagi in 10 blocks of 10 trials. The practices were done over four days and the retention test was conducted 48 hours after the last practice session. The Intrinsic Motivation Inventory was administered to evaluate participants' subjective experience associated with the target task. The task included the ap chagi technique that contained five sub-scales were derived from the evaluation form of World Taekwondo Federation for rating the trials. Mixed and one-way ANOVA models were utilized to analyze the data. Results: The results demonstrated that self-control group have better ap chagi performance during retention test compared to other groups (p = .007). Moreover, the results of intrinsic motivation questionnaire indicated that motivation of self-control group was higher, especially in terms of perceived competence (p = .004) than the other two groups. Conclusion: The results of this study confirmed the usefulness of self-controlled feedback for motor learning by way of an ap chagi technique task. Feedback also affects a learner's intrinsic motivation, which, in turn, seems to improve learning.